Phytoremediation potential of Canavalia ensiformis in copper- and zinc-contaminated soil - Reis Sousa, Rayane (2024)
Soil contamination by heavy metals is an agro–environmental and socioeconomic problem caused by anthropic action on the soil–plant system. More studies on the sustainable use of phytoremediators to remove these metals from the soil environment are needed. Thus, we evaluated the phytoremediation potential of Canavalia ensiformis L. for copper (Cu) and zinc (Zn) metals in the soil. The experiment was conducted in greenhouse, completely randomized design, and five Cu and Zn treatments at increasing doses of 0, 10, 20, 40 and 80 mg kg-1, with four replicates. Growth data (height and number of leaves), dry mass, Cu and Zn concentration in the shoots and roots were assessed. Based on these results, the translocation factor (TF) calculations were performed. C. ensiformis has the potential for phytoextraction because the TF data were >1 for both metals in the shoot tissues of the plant. The highest metals concentrations were observed in the shoots, with a value of 14.13 and 9.36 mg kg-1 for Cu and Zn, respectively. The species had a tolerance index >70% for both metals. In conclusion, the C. ensiformis was efficient in phytoremediation of the evaluated heavy metals, with a progressive translocation process in a concentration–dependent manner.